The Extent of Practicing Transformational Leadership in Palestinian Universities in the Southern Governorates from the Faculty Members' Perspective - Mahmoud Abdel-Majed Assaf; Abdullah Mustafa Hasanein (University of Science and Technology, Yemen, 2019)
The study aimed to determine the degree of faculty members' assessment of practicing transformational leadership in Palestinian universities in the southern governorates, and to explore whether there were statistically significant differences at a level (α≤0.05) attributed to these variables (type of college, academic rank, years of service). To achieve these objectives, the researchers followed the analytical descriptive method by administering a questionnaire consisting of (60) items divided into four areas on a sample of (101) faculty members from these universities (Al-Azhar - Islamic - Al-Aqsa). The results showed that the total degree of assessment of practicing transformational leadership from the point of view of the participants in the universities was medium with a relative weight of 55.93%. The area of independence and influence occupied the first place with a relative weight of 57.75%. The area of presenting a model behavior was ranked last with a relative weight of 54.31%. In addition, there were no statistically significant differences (α≤0.05) between the participants' means of assessment due to these variables: (type of college, rank, years of service). The study recommended enhancing the concepts of transformational discourse in universities based on mutual respect and appreciation of competencies, regardless of any other considerations. Keywords: transformational leadership, Palestinian universities, faculty members.